The making of manhood among Swedish missionaries in China and Mongolia, c. 1890 - c.1914 - Sidenvall, Erik (Studies in Christian mission, 2009)
Introduction-- The Swedish missionary revival in context -- A public missionary and a domestic man, Olof Bingmark, 1875-1900 -- Extending a male private sphere, Otto Oberg, 1869-1917 -- The making of a domestic adventurer, Frans August Larson, 1870-1957 -- Education and the problem of missionary self-making, Alfred Fagerholm, 1871-1923 -- Masculinising missions-consequences and departures